Identification and application of bacterial volatiles to attract a generalist aphid parasitoid: from laboratory to greenhouse assays. Issue 2 (16th October 2020) - Goelen, Tim; Vuts, József; Sobhy, Islam S; Wäckers, Felix; Caulfield, John C; Birkett, Michael A; Rediers, Hans; Jacquemyn, Hans; Lievens, Bart
Abstract: BACKGROUND: Recent studies have shown that microorganisms emit volatile compounds that affect insect behaviour. However, it remains largely unclear whether microbes can be exploited as a source of attractants to improve biological control of insect pests. In this study, we used a combination of coupled gas chromatography‐electroantennography (GC–EAG) and Y‐tube olfactometer bioassays to identify attractive compounds in the volatile extracts of three bacterial strains that are associated with the habitat of the generalist aphid parasitoid Aphidius colemani, and to create mixtures of synthetic compounds to find attractive blends for A. colemani . Subsequently, the most attractive blend was evaluated in two‐choice cage experiments under greenhouse conditions. RESULTS: GC–EAG analysis revealed 20 compounds that were linked to behaviourally attractive bacterial strains. A mixture of two EAG‐active compounds, styrene and benzaldehyde applied at a respective dose of 1 μg and 10 ng, was more attractive than the single compounds or the culture medium of the bacteria in Y‐tube olfactometer bioassays. Application of this synthetic mixture under greenhouse conditions resulted in significant attraction of the parasitoids, and outperformed application of the bacterial culture medium. CONCLUSION: Compounds isolated from bacterial blends were capable of attracting parasitoids both in laboratory and greenhouse assays, indicating that microbial cultures are an effective source of insect attractants. This opens new opportunities to attract and retain natural enemies of pest species and to enhance biological pest control. Abstract : Volatile compounds isolated from bacterial blends are capable of attracting parasitoids. This opens new opportunities to attract and retain natural enemies of pest species and to enhance biological pest control. © 2020 Society of Chemical Industry